Outdoor thermal comfort of open urban squares in moderate and dry climate / Shahab Kariminia - Kariminia, Shahab (Institute of Graduate Studies, UiTM, 2014)
The recent inadvertent development of urban areas alongside the global climate change has highlighted the predominant role of urban climate in the quality of residents’ life. Affected by landscape attributions, anthropogenic heat and urban geometry, the urban climate strongly correlates with outdoor thermal comfort and building’s energy programme. A climate-responsive urban planning ameliorates thermal stress and enhances the social and economic activities accommodated by the cities. Influenced by outdoor thermal comfort, repeated human presence at open urban spaces is a gauge of urban design success. Nevertheless, the available literature studies have mostly addressed either indoor comfort or the energy budget of urban canyons or parks but not much is published on outdoor thermal comfort in the temperate and dry climate of the Middle East. This study aims to present the results of a quantitative empirical outdoor thermal comfort study at two urban squares with focus on the visitors’ thermal sensations.